A hybrid two-layer URANS–LES approach for large eddy simulation at high Reynolds numbers - Temmerman, L.; Hadžiabdić, M.; Leschziner, M.A.; Hanjalić, K. (The International journal of heat and fluid flow, 2005)
A hybrid RANS–LES methodology is proposed for simulating flows that demand a high-quality resolution of the near-wall region. The method allows the thickness of the near-wall RANS Layer to be chosen freely. This layer is interfaced to the outer LES region subject to compatibility conditions for velocity and turbulent viscosity imposed across the interface. These conditions are extracted dynamically as the simulation progresses. In the RANS layer, one-equation ( k– l) and two-equations ( k– ϵ) models are used and interfaced to the dynamic Smagorinsky or one-equation subgrid-scale models. The effectiveness of the method is assessed by reference to fully-developed channel flow at Re b = 10,935 and Re b = 42,200, and a separated flow at Re b = 21,560 in a channel constricted by curved hill-shaped obstructions, for which both pure LES and DES were also performed.